INTERNET DAN PEWARTAAN DALAM PESAN PAUS UNTUK HARI KOMUNIKASI SEDUNIA 2002-2016 - Purwatma, Matheus (Jurnal Orientasi Baru, 2016)
The Message of the Holy Father John Paul II for 36thÂ the World Communication Day 2002, reflects on the means of the Internet for evangelization,